2021
DOI: 10.22219/physiohs.v3i1.16935
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Aktivitas Fisik dengan Kebugaran dan Tingkat Stres pada Karyawan Back Office Rumah Sakit Omni Alam Sutera dimasa Pandemi Covid-19

Abstract: Tujuan: Untuk mengetahui hubungan aktivitas fisik dengan kebugaran dan tingkat stres pada karyawan back office RS. Omni Alam Sutera di masa pandemi covid-19. Metode: Penelitian bersifat deskriptif kuantitatif dengan pendekatan jenis cross sectional study. Total sampel adalah 40 orang karyawan (perempuan n=35 dan laki-laki n=15) dengan usia antara 23-54 tahun. Alat ukur yang digunakan adalah IPAQ untuk mengukur aktivitas fisik, Cooper tes lari 12 menit untuk mengukur kebugaran dan PSS untuk mengukur tingkat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
9
0
4
Order By: Relevance
“…In contrast, this study involves respondents who are school teachers who work hybrid both offline and online. (17,18) This study also found that the quality of sleep did not have a significant relationship with stress during the COVID-19 pandemic. In this study, 90.2% of research subjects had poor sleep quality and most experienced mild stress levels.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, this study involves respondents who are school teachers who work hybrid both offline and online. (17,18) This study also found that the quality of sleep did not have a significant relationship with stress during the COVID-19 pandemic. In this study, 90.2% of research subjects had poor sleep quality and most experienced mild stress levels.…”
Section: Discussionmentioning
confidence: 58%
“…Sebanyak 59% orang dewasa pekerja kantoran termasuk dalam kategori aktivitas fisik yang ringan [29]. Pegawai yang mempunyai aktivitas ringan memiliki resiko kebugaran yang kurang sebesar 10 kali dibanding dengan aktivitas sedang dan tinggi [30].…”
Section: Pembahasanunclassified
“…Like physical activity, workers' sitting time from January to December 2022 increased by almost 2 hours daily. (5) Setiawan et al, 2021 show that most workers have physical activity in the light category, less than half are in the moderate category, and only a small number are in the high category. The research results also report a relationship between physical activity, fitness levels, and stress.…”
Section: Study Characteristicsmentioning
confidence: 99%